2019
DOI: 10.32479/irmm.7871
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Dining Satisfaction by Understanding Diner Hygiene Expectation and Experience

Abstract: Indian Muslim eateries are a prominent part of Malaysian food culture and gastronomic tourism. However, according to the local the news, these eateries are plagued with negative hygienic issues. As this could endanger the diner's overall health and well-being, it is a serious concern. Therefore, this study posits hygiene expectation and hygiene experience as the primary determinants of diner satisfaction. Expectation disconfirmation theory was used as a theoretical base for this study, as it allows the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In this study, it was determined that although all expectations were higher than the service experienced, expectations regarding price, cleanliness and professional appearance of employees were significantly lower than the service experienced. In the literature, there are studies to determine the level of meeting the expectations of restaurant customers regarding online meetings (Li, Xie, & Zhang, 2020), service quality (Markovi c, Raspor, & Segari c, 2010), restaurant features (Mhlanga, Hattingh, & Moolman, 2014) and hygiene (Chow, Krishnapillai, & Lee, 2019). There are studies that are like the findings of this study.…”
Section: Ihrsupporting
confidence: 54%
“…In this study, it was determined that although all expectations were higher than the service experienced, expectations regarding price, cleanliness and professional appearance of employees were significantly lower than the service experienced. In the literature, there are studies to determine the level of meeting the expectations of restaurant customers regarding online meetings (Li, Xie, & Zhang, 2020), service quality (Markovi c, Raspor, & Segari c, 2010), restaurant features (Mhlanga, Hattingh, & Moolman, 2014) and hygiene (Chow, Krishnapillai, & Lee, 2019). There are studies that are like the findings of this study.…”
Section: Ihrsupporting
confidence: 54%
“…When consumers are satisfied with the performance of a product or service, they are likely to repurchase because the performance meets their expectations (Anderson and Sullivan, 1993; Oliver, 1980). Several studies have shown that consumers’ overall satisfaction was impacted by positive disconfirmation in several areas including retailing (Anderson and Sullivan, 1993), leadership style (Wong and Giessner, 2018), hygiene expectation and experience (Chow et al , 2019), information technology (Bhattacherjee, 2001), online travel agents (McKinney et al , 2002), online review and opinions (Lee and Kim, 2020; Li et al , 2020) and other service providers (Susarla et al , 2003). Extensive consumer satisfaction research has concluded that expectation is a key for confirming satisfaction, which can be either a positive disconfirmation (perceived performance is more than one’s expectation) or a negative disconfirmation (perceived performance is below one’s expectation) (Yuksel and Yuksel, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tangari et al (2019) confirmed that calories per serving information created a consumption backfire when it was disconfirmed. In restaurant cleanliness research, Chow et al (2019) found that a cleanliness expectation had a significant positive impact on consumers’ satisfaction. Another EDT study confirmed cleanliness is a significant predictor in determining customer satisfaction (Tama, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The article (Chow & Lee, 2019) describes the method of refuting expectations, as a theoretical basis for postulating the interaction between expectation and experience and its impact on issues related to tourism.…”
Section: Methodsmentioning
confidence: 99%